2020
DOI: 10.5093/jwop2020a12
|View full text |Cite
|
Sign up to set email alerts
|

Unique Contextual Conditions Affecting Coworker Knowledge Sharing and Employee Innovative Work Behaviors

Abstract: Drawing on a componential model of creativity, this study examines how coworker knowledge sharing drives employee innovative work behaviors in the workplace. Furthermore, the moderating effect of situational factor (supervisor knowledge sharing) and personal factor (employee thriving) were analyzed to explore the unique contextual conditions which could influence this relationship. A sample of 374 employees across a variety of jobs and industries was used to test these relationships. Supervisor knowledge shari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
3
0
1
Order By: Relevance
“…The results further demonstrated that thriving at the workplace has a significant and positive effect on IWB. The results are parallel with the findings of Abid et al (2015) and Shah et al (2020). This is because productivity, being open to challenges and having the chance to learn and grow continually increase the ability of the employee to work with innovative concepts, hence novel commodities, methods, and procedures are introduced and applied to a person's job position, work unit, or company.…”
Section: Direct-effect Estimation Using Pls Bootstrappingsupporting
confidence: 83%
“…The results further demonstrated that thriving at the workplace has a significant and positive effect on IWB. The results are parallel with the findings of Abid et al (2015) and Shah et al (2020). This is because productivity, being open to challenges and having the chance to learn and grow continually increase the ability of the employee to work with innovative concepts, hence novel commodities, methods, and procedures are introduced and applied to a person's job position, work unit, or company.…”
Section: Direct-effect Estimation Using Pls Bootstrappingsupporting
confidence: 83%
“…Third, this study employed POP as a moderating variable that augmented KH behavior in self-serving employees. Variables, such as thriving at work, 128 or perceived mastery climate 129 may also be added as buffers to exert negative effect on KH. Fourth, this survey-based study gathered data from knowledge intensive firms of Pakistan, which might call the issue of generalizability.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Through conversations in sharing information between colleagues about professional zakat, of course this is a potential trigger in attracting the interest of other colleagues to pay professional zakat (Shah et al, 2020). Based on Reasoner et al ( 2022) A person's intention to pay zakat arises by considering environmental factors.…”
Section: Subjective Normsmentioning
confidence: 99%